Phylogeographic Evidence for 2 Genetically Distinct ZoonoticPlasmodium knowlesiParasites, Malaysia - Yusof, Ruhani; Ahmed, Md Atique; Jelip, Jenarun; Ngian, Hie Ung; Mustakim, Sahlawati; Hussin, Hani Mat; Fong, Mun Yik; Mahmud, Rohela; Sitam, Frankie Anak Thomas; Japning, J. Rovie-Ryan; Snounou, Georges; Escalante, Ananias A.; et al. (Centers for Disease Control and Prevention, 2016)
Infections of humans with the zoonotic simian malaria parasite Plasmodium knowlesi occur throughout Southeast Asia, although most cases have occurred in Malaysia, where P. knowlesi is now the dominant malaria species. This apparently skewed distribution prompted an investigation of the phylogeography of this parasite in 2 geographically separated regions of Malaysia, Peninsular Malaysia and Malaysian Borneo. We investigated samples collected from humans and macaques in these regions. Haplotype network analyses of sequences from 2 P. knowlesi genes, type A small subunit ribosomal 18S RNA and cytochrome c oxidase subunit I, showed 2 genetically distinct divergent clusters, 1 from each of the 2 regions of Malaysia. We propose that these parasites represent 2 distinct P. knowlesi types that independently became zoonotic. These types would have evolved after the sea-level rise at the end of the last ice age, which separated Malaysian Borneo from Peninsular Malaysia.